2018
DOI: 10.18632/oncotarget.25998
|View full text |Cite
|
Sign up to set email alerts
|

Bladder cancer detection by urinary extracellular vesicle mRNA analysis

Abstract: ObjectiveUrinary extracellular vesicles (EV) could be promising biomarkers for urological diseases. In this retrospective feasibility study, we conducted biomarker screening for early stage bladder cancer using EV mRNA analysis.MethodsBiomarker candidates were identified through RNA-seq analysis of urinary EV from patients with non-muscle invasive bladder cancer (N=3), advanced urothelial cancer (N=3), no residual tumor after TURBT (N=2), and healthy and disease controls (N=4). Diagnostic performance was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
(35 reference statements)
1
22
0
Order By: Relevance
“…Moreover, KRT17 expression is correlated with triplenegative breast cancer and predicts poor prognosis [14]. In our present study, higher KRT17 expression was found in BCa cells than normal human urothelial cell, similarly as shown by Murakami et al [15] and Babu et al [16]. Together, these findings may imply the potential role of KRT17 in the bladder tumorigenesis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, KRT17 expression is correlated with triplenegative breast cancer and predicts poor prognosis [14]. In our present study, higher KRT17 expression was found in BCa cells than normal human urothelial cell, similarly as shown by Murakami et al [15] and Babu et al [16]. Together, these findings may imply the potential role of KRT17 in the bladder tumorigenesis.…”
Section: Discussionsupporting
confidence: 89%
“…The aberrant expression of KRT17 has been investigated in various carcinomas, and could serve as a potential diagnostic and prognostic marker, including cervical carcinoma, breast cancer and oral carcinoma [12][13][14]. A recent study based on RNA-seq analysis of urinary extracellular vesicle mRNA from patients with urological diseases identified the overexpression of KRT17 in high stage BCa [15]. Moreover, KRT17 has been recognized as a sensitive and specific biomarker in diagnosis of urothelial neoplasia, and muscle-invasive urothelial carcinoma had a higher proportion of positive KRT17 detection than the non-muscle-invasive type [16].…”
Section: Introductionmentioning
confidence: 99%
“…In urine from patients with a muscle-invaded bladder cancer, 529 mRNAs and 9 mRNAs were significantly upregulated and downregulated, respectively, compared to urine from healthy volunteers (Figure 6D). Some of the upregulated mRNAs, such as MDK, SLC2A1, GPRC5A, KRT17, and KRT5, have been reported in urine and were suggested as biomarkers for the accurate detection and classification of bladder cancer (Eckstein et al, 2018;Holyoake et al, 2008;Lin et al, 2019;Murakami et al, 2018). In CSF from glioblastoma patients, only 2 mRNAs are significantly upregulated compared to that in CSF from hydrocephalus patients.…”
Section: Assessment Of the Tissues Of Origin And Deconvolution Of Pancreatic Cyst Fluidmentioning
confidence: 99%
“…One of these cancer-related genes detected in urinary EVs is SLC2A1 . Other genes, such as GPRC5A and KRT17, are overexpressed in stage pT1 and advanced BC 44 . These results provide the potential for EVs as biomarkers for detecting non-muscle invasive bladder cancer and muscle-invasive bladder cancer.…”
Section: Components Of Urine Biopsymentioning
confidence: 99%